Drivers of changes in agricultural intensity in Europe. (15th December 2016) - Levers, Christian; Butsic, Van; Verburg, Peter H.; Müller, Daniel; Kuemmerle, Tobias
Highlights: Substantial yields increase and nitrogen application decrease in Europe 1990–2007. Agricultural intensity higher in Europe's west compared to the east. Increasing yield mainly related to fertiliser input, climate, and micro-economy. Nitrogen application declines mostly related to soil, climate, and farm characteristics. Diverging intensity trends suggest a de-coupling of output from input intensity. Abstract: The global demand for agricultural products will increase in the 21st century, unless major transformations in consumptive behaviour occur. To a large extent, production increases in agriculture will depend on intensifying existing agricultural systems. Yet, our understanding of what determines the spatial patterns of agricultural intensity and changes therein is limited. Here, we analysed agricultural intensity changes in Europe focussing on yields and fertiliser application for six major crop-type groups for the period 1990–2007. We applied random effects panel regressions to analyse the spatial determinants of intensity changes using a suite of biophysical and socio-economic variables. We found that yields increased and mineral nitrogen application decreased by approximately 10%, suggesting a decoupling of changes in output and input intensity in Europe's agricultural systems. Yields and nitrogen application across crop-type groups were particularly high in Western and Central Europe, whereas Eastern Europe was characterised by lower yields and nitrogen application. We also found strong sub-national variation in intensity levels in respect to crop-type groups and indicators. Higher yields were typically related to higher fertilisation, high soil quality, less growing degree days, and high labour productivity. Higher nitrogen application rates, in turn, were related to high soil water and carbon contents, and high labour productivity. Our study provides insights into broad-scale agricultural intensity patterns in Europe that allow for identifying trade-offs between agriculture and the environment, as well as entry points for regionalised, targeted policy making towards a more sustainable management of Europe land systems.